WSAgent: um agente baseado em Web Services para promover a interoperabilidade entre sistemas heterogêneos no domínio da saúde - Rheinheimer, Letícia Rafaela (Universidade do Vale do Rio do Sinos, 2004)
After the Internet advent, several strategies about software development were changed to promote more reuse and interoperability. Design Patterns and Frameworks help us to create software and design flexible. The idea of glue applications to work together is very attractive. In the health domains, there are many drawbacks to address its goals. The use of agent technologies combined with Web Services allow us to think about the construction of a bind to grant interoperability, reuse and flexibility between heterogeneous environments. This work describes the architecture of a software agent called WSAgent – an instance of a Framelet of Patient subdomain in Health domain – and its strategies of collaborations and interoperability. This work also presents a case study with the implementation of a prototype
Keywords: agentes de software; bases de dados heterogêneas; design patterns; ontologias; web services; Desenvolvimento de sistemas; frameworks; design patterns; heterogeneous databases; ontologies; software agents; web services; frameworks; Ciências Exatas e da Terra